BTEC First Health and Social Care. Student textbook - Walsh, Mark, 1963- (London : Collins Educational, 2010)
Provide your students with a strong and distinctive case study approach which will contextualise key issues with this textbook for BTEC First Health and Social Care. Attract students by putting learning into context around scenarios that engage students' human interest and caring values.
Keywords: Medical care; Social service; Health and Wellbeing